Pendekatan Taghrīb dan Tarhīb dalam Penyampaian Dakwah - Syed Hussin, Syed Abdurahman (Jurnal Usuluddin, 2005)
The paper attempts to elaborate the concept of taghrib and tarhib as methods of approach in dakwah to three groups of people: the intelectuals, the public and the antagonist. In the paper, taghrib is defined as inculcating inclination or persuasion and tarhib as indicating danger or warning. The two approaches should be effectively applied as the situation warranted and in the implementation the methods of al-hikmah (wisdom), mawizah hasanah (advice) and mujadalah bi al-husna (dialog) should be considered and appropriately used. Some evidences from the Quran and incidents in history are used to clarify certain points in discussion.